The impact of Motivational Scaffolding on Self-efficacy and Learning Achievement of Field Dependent/ Independent EFL Learners - Masoumeh Sohrabi; Hossein Siahpoosh; Asgar Mahmoudi (Journal of English Language Pedagogy and Practice, 2022)
The study investigated the impacts of motivational scaffolding as one of the most effective instructional procedures on self-efficacy and learning achievement of field-dependent and field-independent English language learners. This study attempted to use both qualitative and quantitative data to get more reliable results. As qualitative part, 15 teachers in a semi-structured interview, and as quantitative part, two groups of learners participated as experimental and control groups. Motivated Strategies for Learning Questionnaire was used to determine students' self-efficacy. The Group Embedded Figures Test was administered to categorize them into groups of field-dependent and field-independent. To determine proficiency level, a pre-test and a post-test were used. As treatment, eight sessions of Bandura’s training were administered to improve self-efficacy. Analysis of the qualitative data was conducted using content analysis, and as quantitative analysis, two-way Multivariate Analysis of Variance was conducted. The results showed that learners’ interacting within motivational scaffolding improved their self-efficacy and their learning achievement, and there is no significant difference between learners in the dimensions of field-dependent, field-independent. The findings have implications for teachers and learners in educational settings to detect some factors affecting the English language learners’ language performance and their psychological status.